50th AIAA/ASME/SAE/ASEE Joint Propulsion Conference 2014
DOI: 10.2514/6.2014-4029
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous Thrust Production from an RF Test Device Measured on a Low-Thrust Torsion Pendulum

Abstract: This paper describes the eight-day August 2013 test campaign designed to investigate and demonstrate viability of using classical magnetoplasmadynamics to obtain a propulsive momentum transfer via the quantum vacuum virtual plasma. This paper will not address the physics of the quantum vacuum plasma thruster, but instead will describe the test integration, test operations, and the results obtained from the test campaign.Approximately 30-50 micro-Newtons of thrust were recorded from an electric propulsion test … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
37
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(40 citation statements)
references
References 1 publication
2
37
0
1
Order By: Relevance
“…Moreover our early works based on huge automatic collected data by using very advanced accelerometers [19][20][21] also corroborate the existence of Biefeld-Brown effect. It is also important to mention that similar effects have been reported in literature -although they have features that cannot be directly associated with BB effect -in some alternative experimental devices and experiments, e. g., the detection of anomalous forces in superconducting ceramic disks [23,24], superconducting toroids in rotation [25], thrusts in EM Drives [26,27] and the early cited superconducting device with different layers [17] that simulates the capacitive effect needed to raise the anomalous forces of BB effect. The importance of verification of BB effect existence is doubtless unquestionable because it will probably provide us with a new valuable resource for technological applications as the propulsion ones.…”
Section: Fig 1: Scheme Of (A) Symmetrical and (B) Asymmetrical Capacsupporting
confidence: 59%
“…Moreover our early works based on huge automatic collected data by using very advanced accelerometers [19][20][21] also corroborate the existence of Biefeld-Brown effect. It is also important to mention that similar effects have been reported in literature -although they have features that cannot be directly associated with BB effect -in some alternative experimental devices and experiments, e. g., the detection of anomalous forces in superconducting ceramic disks [23,24], superconducting toroids in rotation [25], thrusts in EM Drives [26,27] and the early cited superconducting device with different layers [17] that simulates the capacitive effect needed to raise the anomalous forces of BB effect. The importance of verification of BB effect existence is doubtless unquestionable because it will probably provide us with a new valuable resource for technological applications as the propulsion ones.…”
Section: Fig 1: Scheme Of (A) Symmetrical and (B) Asymmetrical Capacsupporting
confidence: 59%
“…T WAS previously reported that radio-frequency (RF) resonant cavities generated anomalous thrust on a low-thrust torsion pendulum [1,2] in spite of the apparent lack of a propellant or other medium with which to exchange momentum. It is shown here that a dielectrically loaded, tapered RF test article excited in the transverse magnetic 212 (TM212) mode (see Fig.…”
mentioning
confidence: 99%
“…A discussion of spacecraft "conservation of energy" is given in Appendix A. Recent laboratory test results [2] indicate the expected thrust-to-power ratio for flight applications could be in the 0. 4 -4.0 N/kWe range, which is one to two orders of magnitude greater than current operational electric thrusters.…”
Section: Introduction Q-thruster Overviewmentioning
confidence: 99%